2005
DOI: 10.1021/jm050462t
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Series of Non-Carboxylic Acid, Non-Hydantoin Inhibitors of Aldose Reductase with Potent Oral Activity in Diabetic Rat Models:  6-(5-Chloro-3-methylbenzofuran-2-sulfonyl)-2H-pyridazin-3-one and Congeners

Abstract: Discovery of a highly selective, potent, and safe non-carboxylic acid, non-hydantoin inhibitor of aldose reductase (AR) capable of potently blocking the excess glucose flux through the polyol pathway that prevails under diabetic conditions has been a long-standing challenge. In response, we did high-throughput screening of our internal libraries of compounds and identified 6-phenylsulfonylpyridazin-2H-3-one, 8, which showed modest inhibition of AR, both in vitro and in vivo. Initial structure-activity relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 55 publications
0
23
0
3
Order By: Relevance
“…Alternatively, the past failures may simply reflect insufficient inhibition of the pathway in target tissues by the doses of drugs used in humans (6). Of the two chemical classes of ARIs tested to date in phase III trials, the carboxylic acid inhibitors (e.g., zopolrestat) penetrate tissues poorly and are not very potent in vivo, whereas the spiroimide (spirohydantoin) inhibitors penetrate tissues more efficiently, but many have caused skin reactions or liver toxicity that limited the doses usable in humans to doses that were subtherapeutic in animal models (7,8). For example, the dose of sorbinil that was used in the essentially negative Sorbinil Retinopathy Trial (8) is ϳ20-fold lower than the dose shown to prevent retinal polyol pathway activation and the development of retinopathy in diabetic rats (1,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the past failures may simply reflect insufficient inhibition of the pathway in target tissues by the doses of drugs used in humans (6). Of the two chemical classes of ARIs tested to date in phase III trials, the carboxylic acid inhibitors (e.g., zopolrestat) penetrate tissues poorly and are not very potent in vivo, whereas the spiroimide (spirohydantoin) inhibitors penetrate tissues more efficiently, but many have caused skin reactions or liver toxicity that limited the doses usable in humans to doses that were subtherapeutic in animal models (7,8). For example, the dose of sorbinil that was used in the essentially negative Sorbinil Retinopathy Trial (8) is ϳ20-fold lower than the dose shown to prevent retinal polyol pathway activation and the development of retinopathy in diabetic rats (1,9).…”
mentioning
confidence: 99%
“…1) (7) and reported to prevent elevated urinary albumin excretion in diabetic rats (15,16). CP-744809, or compound 19m (7) (henceforth referred to as ARI-809), is a sulfonylpyridazone that in initial characterization studies was profiled as one of the most potent and selective ARIs yet described (7). ARI-809 is a highly selective (1:930) (7) inhibitor of aldose reductase relative to aldehyde reductase, and such selectivity distinguishes it from sorbinil, which inhibits aldose and aldehyde reductase to a comparable extent (11).…”
mentioning
confidence: 99%
“…Carboxylic acidic inhibitors, such as zopolrestat, ponalrestat, and tolerestat have poor tissue penetration and do not exert very potent in vivo effects. Spiroimide inhibitors, such as sorbinil, penetrate tissues more efficiently, while unfortunately generating allergic skin reaction and kidney toxicity (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the most potent and selective compound was profiled to be 6-(5-chloro-3-methylbenzofuran-2-sulfonyl)-2H-pyridazin-3-one (ARI-809) with IC50 value of 1 nM in vitro and ED50 of 0.8 mg/kg in vivo. ARI-809 is a highly selective (1:930) inhibitor of AR relative to aldehyde reductase, and such selectivity distinguishes it from sorbinil, which inhibits AR and aldehyde reductase to a comparable extent [73,74]. In addition, introduction of phenol moiety into the sulfonyl-bridged system has provided benzenesulfonamide ARIs, which could not only inhibit AR but also exhibit potent antioxidant activity [75].…”
Section: Ar Inhibitorsmentioning
confidence: 99%